Stroke thrombectomy volume, rather than stroke center accreditation status of hospitals, is associated with mortality and discharge disposition. (1st March 2022) - Waqas, Muhammad; Tutino, Vincent M; Cappuzzo, Justin M; Lazarov, Victoria; Popoola, Daniel; Patel, Tatsat R; Levy, Bennett R; Monteiro, Andre; Mokin, Maxim; Rai, Ansaar T; Mocco, J; Turk, Aquilla S; et al.
Abstract : Background: Few studies have explored the association between stroke thrombectomy (ST) volume and hospital accreditation with clinical outcomes. Objective: To assess the association of ST case volume and accreditation status with in-hospital mortality and home discharge disposition using the national Medicare Provider Analysis and Review (MEDPAR) database. Methods: Rates of hospital mortality, home discharge disposition, and hospital stay were compared between accredited and non-accredited hospitals using 2017–2018 MEDPAR data. The association of annual ST case volume with mortality and home disposition was determined using Pearson's correlation. Median rate of mortality and number of ST cases at hospitals within the central quartiles were estimated. Results: A total of 29 355 cases were performed over 2 years at 847 US centers. Of these, 354 were accredited. There were no significant differences between accredited and non-accredited centers for hospital mortality (14.8% vs 14.5%, p=0.34) and home discharge (12.1% vs 12.0%, p=0.78). A significant positive correlation was observed between thrombectomy volume and home discharge (r=0.88; 95% CI 0.58 to 0.97, p=0.001). A significant negative relationship was found between thrombectomy volume and mortality (r=−0.86; 95% CI −0.97 to −0.49, p=0.002). Within the central quartiles, the median number of ST cases at hospitals with mortality was 24/year, and the median number of ST cases at hospitals with home discharge rate was 23/year. Conclusion: A higher volume of ST cases was associated with lower mortality and higher home discharge rate. No significant differences in mortality and discharge disposition were found between accredited and non-accredited hospitals.